(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Kamala Markandaya has successfully represented and depicted human relationship in her novels. Keeping her works and the major themes, I would like to evaluate its significance in this post - modernist society. Her portrayal of human relations and human bonds is remarkable as she allows her characters to follow their own minds and face life naturally and bravely.